The committed enterprise : - Davidson, J. H. (J. Hugh) (Butterworth-Heinemann, 2002)
The Committed Enterprise represents Hugh Davidson's major statement on what makes a sustainable and excellent organization. It is based on over a year of intense fieldwork during which the author interviewed in person the most senior executives in 126 organizations in the US and Europe. It is much easier to describe vision and values than implement them. Vision and values management is in the dark ages compared with that of Marketing, Finance or Operations. It is often derided and all too often just doesn't work. The Committed Enterprise takes a hard approach to this 'soft' topic and describes how to build unstoppable organisations, whether businesses or charities, hospitals or orchestras, by managing vision and values scientifically yet creatively. It shows how to lay the foundations for success by understanding the conflicting needs of stakeholders and uniting them through the right vision and values. These forge uncompromising commitment, and transform organizations, teams and countries.